Metabolic Profiling of Three Species of Amorphophallus (Araceae) - Santosa, Edi; Fatah, Muhammad; Kuswanto, Lianah; Krisantini, Krisantini (Journal of Tropical Crop Science, 2022)
A study was conducted to determine the metabolic contents of corms of three species of Amorphophallus, A. muelleri, A. paeoniifolius, and A. variabilis using gas chromatography mass spectrometry (GCMS) with water as polar solvent. The corms were collected from plants cultivated at the Leuwikopo Experimental Station, IPB University, Darmaga, Bogor, Indonesia. Metabolic profiling conducted at the Jakarta Regional Health Laboratory, Indonesian Ministry of Health, demonstrated that the three species of Amorphophallus vary in metabolic content, specifically for 12 compounds belonging to antioxidants, vitamins, saturated fatty acids, polyunsaturated fatty acids, phytosterol, alcohol, aldehyde, and alkane. Our study had shown that metabolic profiling is a potentially useful method of differentiating or determining species markers that in turn could be efficient way for genetic conservation and development of future food source.